Identifying the Meaning of Work Factors among Lecturer Profession - Ersaliya Arezah; Wina Diana Sari (ARRUS Journal of Social Sciences and Humanities, 2024)
Lecturers as the central position of educators have noble duties. In reality, regulations related to lecturer careers management, clarity of the lecturer profession, are starting to erode the essence of an educator in the lecturer profession. This research using a qualitative approach with systematic analysis that aims to identify the value of meaning of work for lecturers in the onslaught of workload, regulations and ambiguity experienced by lecturers today. Based on interviews and data analysis, the three values of meaningful work among lecturers are internalization of the profession, lifelong learning, and personal integrity. This research is expected to be a consideration for policy makers in formulating regulations for the teaching profession.